Surviving Complications of Retroperitoneal Fibrosis with Intermittent Relapses over a Period of 20 years: Case report and literature Review: Is it chronic progressive disease or intermittent relapses every time encasing a new structure? (International Journal of Medical and Surgical Sciences, 2021)
Idiopathic retroperitoneal fibrosis is a rare fibro-inflammatory disease of varied etiology which usually originates around aorta and spreads caudally along Iliac vessels into adjacentretroperitoneum causing ureteral obstruction as the most frequent complication.A 53-year-old male patient presented with complaint of mild pain in both the legs off and on. On investigating further, we found that he had been struggling with intermittent relapses every 3-4 years for last 20 years since he was first diagnosed with Idiopathic Retroperitoneal Fibrosis. He was33-year-old when he first developed the symptoms of anuria for 48 hours and was diagnosed with Idiopathic retroperitoneal fibrosis. This was followed by atrophy of left kidney and hypertension 6 years later, then hypothyroidism after another 3years and finally involvement of Inferior VenaCava and acute Deep Vein Thrombosis of lower limbs after another 3-4 years. His deep vein thrombosis was well managed in time. He was put on glucocorticoids everytime he had a relapse and a complication.We did a review of literature to understand recent advances about its pathogenesis, diagnosis, investigations and management. We searched in PubMed using terms like retroperitoneal fibrosisalone and in combination with related terms such as Inferior Vena Cava thrombosis, Deep Vein Thrombosis, Tamoxifen, Methotrexate. This case is unique as it is very rare to find acute Deep Vein Thrombosis in Idiopathic retroperitoneal fibrosis without development of any collateralswhen Inferior Vena Cava lumen is compromised to almost complete obstruction. After a follow up of 20 years patient is doing well in terms of physical activity and psychologicalwellbeing with anti-hypertensives, thyroxine and anti-coagulants. Is the disease-free interval actually free of the disease or it just subsided with immunosuppressants to become active after some time?
Keywords: Idiopathic Retroperitoneal Fibrosis; Inferior Vena Cava thrombosis; Hypothyroidism; Immunosuppressants; Obstructive uropathy; retroperitoneal fibrosis